Freeze-Out Parameters in Heavy-Ion Collisions at AGS, SPS, RHIC, and LHC Energies. (9th June 2015) - Chatterjee, Sandeep; Das, Sabita; Kumar, Lokesh; Mishra, D.; Mohanty, Bedangadas; Sahoo, Raghunath; Sharma, Natasha
Abstract : We review the chemical and kinetic freeze-out conditions in high energy heavy-ion collisions for AGS, SPS, RHIC, and LHC energies. Chemical freeze-out parameters are obtained using produced particle yields in central collisions while the corresponding kinetic freeze-out parameters are obtained using transverse momentum distributions of produced particles. For chemical freeze-out, different freeze-out scenarios are discussed such as single and double/flavor dependent freeze-out surfaces. Kinetic freeze-out parameters are obtained by doing hydrodynamic inspired blast wave fit to the transverse momentum distributions. The beam energy and centrality dependence of transverse energy per charged particle multiplicity are studied to address the constant energy per particle freeze-out criteria in heavy-ion collisions.